(untitled) (Altre Modernità, 2025)
With Via Gemito, a new phase of Domenico Starnone’s novel begins. From 2001 until now, spanning approximately twenty years, the writer’s narrative production has exhibited constant thematic and structural elements that suggest the existence of a specific figurative and lexical repertoire. In his presentation for the Seminar on Short Stories organized by Luigi Rustichelli in 1992, a period preceding what is commonly associated with his strictly defined novelistic production, Starnone speaks of ‘little facts’, which are actual events – often jotted down on scraps of paper and later abandoned in drawers – that serve as the foundation for every story. The writer’s skill, and thus the narrator’s credibility, lies precisely in the ability to manipulate these ‘little facts’ and incorporate them into a structured narrative framework, giving them meaning and, more importantly, constructing an ending. This analysis will focus on a particular figure, that of the girl from Milan, which appears with some variations in Via Gemito and Labilità, and finds its full realization in the short story published by Einaudi in 2021, Vita mortale e immortale della bambina di Milano (Mortal and Immortal Life of the Girl from Milan). By reconstructing one of these ‘little facts’, we will be able to assess Starnone’s experiential and linguistic repertoire. We will examine how each novel draws from a unique pool of events and words, and how fiction is brought to life through precise manipulation and assembly.